A review on industrial scale anaerobic digestion systems deployment in Malaysia: Opportunities and challenges - Kumaran P.; Hephzibah D.; Sivasankari R.; Saifuddin N.; Shamsuddin A.H. (Elsevier Ltd, 2023)
Biogas; Carbon dioxide; Electric power generation; Emission control; Energy policy; Methane; Renewable energy resources; Waste disposal; Waste management; Waste treatment; Wastewater treatment; Water treatment; Anaerobic digestion technology; Clean Development Mechanism; Electricity generation capacity; Feed-in tariff; Renewable energies; Renewable energy generation; Research and development; Waste to energy; Anaerobic digestion